Mixed convection in a two-sided elastic walled and SiO2 nanofluid filled cavity with internal heat generation: Effects of inner rotating cylinder and nanoparticle's shape - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2015)
In this study, mixed convection in a cavity with volumetric heat generation and filled with nanofluid having an inner rotating cylinder and two flexible side walls is numerically investigated. The top wall of the cavity is at constant cold temperature while the bottom wall is kept at hot temperature. Two flexible side walls and the surface of the inner rotating cylinder are accepted as adiabatic. The finite element formulation is used to solve the governing equations. The Arbitrary-Lagrangian-Eulerian method is used to describe the fluid motion with the flexible side walls of the cavity in the fluid-structure interaction model. The influence of external Rayleigh number, elastic modulus pair of the flexible side walls, angular rotational speed of the cylinder, internal Rayleigh number and nanoparticle volume fraction on the fluid flow and heat transfer are numerically simulated by using different solid nanoparticle shapes (spherical, cylindrical, brick and blade type). It is observed that the local and averaged heat transfer enhances as the external Rayleigh number, nanoparticle volume fraction and absolute value of the angular rotational velocity of the cylinder increase and as the internal Rayleigh number decreases. The elastic modulus of the side walls can be used to control the fluid flow and heat transfer inside the cavity. Utilizing cylindrical nanoparticles gives the best performance in terms of heat transfer enhancement. © 2015 Elsevier B.V. All rights reserved.
Keywords: Finite element formulation; Fluid-structure interaction; Mixed convection; Nanoparticle shape